THE ROLE OF INFLUENCERS TO INCREASE SALES OF GOODS AND SERVICE - Siera, Siera Syailendra; Ahmad Sopyan; Alfindo, Rezky; Rizky, Melita (Jurnal Manajemen Bisnis dan Terapan, 2000)
With increasing levels of digital media consumption, organizational spending on online promotion continues to grow steadily and dynamically. However, in line with this growth in spending, it is clear that the effectiveness of promotional activities in the digital world has decreased. Today, organizations are looking for alternatives to influence consumers in an increasingly complex market. One of the key trends emerging is the adoption of the influencer marketing concept. The purpose of this article is to analyze the role, position and significance of digital influencers in the overall functioning of the online promotion system, as well as the impact of the influencer marketing concept on sustainable development. A literature analysis was conducted to understand the origins of this phenomenon, along with its scale, causes and impact on the functioning of the digital promotion system. After completing this stage, a questionnaire survey was conducted among a group of individual internet users to obtain primary data. The research findings show great potential in activities involving digital influencers. This potential is mainly related to the effective delivery of information regarding products or services, their impact on increasing brand awareness, and their influence on the sales of the company's products and services. This research confirms that digital marketing strategies involving influencers can achieve success, where influencers play a key role in persuading potential buyers through promotions on social media. The findings make a significant contribution to understanding the integration of influencers' roles in digital marketing strategies to achieve increased sales.